In Vivo Evaluation of Antirrhinum majus' Wound-Healing Activity - Fadi G. Saqallah; Wafaa M. Hamed; Wamidh H. Talib (MDPI AG, 2018)
Mediterranean-native perennial plant Antirrhinum majus was scrutinized in this study for its antioxidant activity and its total phenolic content in order to test for the plant’s wound-healing capability. The traditional uses of this plant to treat gum scurvy, various tumors, ulcers, and hemorrhoids were the main idea behind this study. Leaves and flowers of the A. majus were extracted by maceration. Pilot qualitative phytochemical tests were made to check the presence of various secondary metabolites. Quantitatively, the flowers’ macerate indicated superlative results regarding antioxidant activity and total phenolic content. However, the in vivo wound-healing capability study was made using 30 Wistar strain albino rats. This innovative part of the study revealed that the healing power of the flowers’ extract ointment (5% w/w) was superior compared to the leaves’ extract (5% w/w) and the positive-control ointments (MEBO) (1.5% w/w) (p ≤ 0.001). This activity was assessed by visual examination, wound-length measurement, and estimation of hydroxyproline content. Antirrhinum majus is a promising plant to be considered for wound healing. However, further testing (including histological examination and high-performance liquid chromatography (HPLC) analysis) is necessary to understand more about its mechanisms of action.